2006
DOI: 10.1007/s00418-006-0177-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of β-bungarotoxin, or geniculate ganglion lesion on taste bud development in the chick embryo

Abstract: Chick taste bud (gemmal) primordia normally appear on embryonic day (E) 16 and incipient immature, spherical-shaped buds at E17. In ovo injection of beta-bungarotoxin at E12 resulted in a complete absence of taste buds in lower beak and palatal epithelium at developmental ages E17 and E21. However, putative gemmal primordia (solitary clear cells; small, cell groupings) remained, lying adjacent to salivary gland duct openings as seen in normal chick gemmal development. Oral epithelium was immunonegative to neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 96 publications
(123 reference statements)
0
1
0
Order By: Relevance
“…These results suggested that AADC expression begins at early stages of taste bud cell diVerentiation, and biogenic amines may act on taste bud diVerentiation of tongue epithelial cells. Taste bud development in chick was investigated by Ganchrow et al (2006) who found evidence that taste bud maturation, maintenance and survival are nerve-dependent.…”
mentioning
confidence: 99%
“…These results suggested that AADC expression begins at early stages of taste bud cell diVerentiation, and biogenic amines may act on taste bud diVerentiation of tongue epithelial cells. Taste bud development in chick was investigated by Ganchrow et al (2006) who found evidence that taste bud maturation, maintenance and survival are nerve-dependent.…”
mentioning
confidence: 99%